Loss of fatty acid binding protein-1 alters the hepatic endocannabinoid system response to a high-fat diet - Martin, Gregory G. (J Lipid Res, 2017)
Upregulation of the hepatic endocannabinoid (EC) receptor [cannabinoid receptor-1 (CB1)] and arachidonoylethanolamide (AEA) is associated with nonalcoholic fatty liver disease (NAFLD). Male mice fed high-fat diet (HFD) ad libitum also exhibit NAFLD, increased hepatic AEA, and obesity. But, preference for HFD complicates interpretation and almost nothing is known about these effects in females. These issues were addressed by pair-feeding HFD. Similarly to ad libitum-fed HFD, pair-fed HFD also increased WT male and female mouse fat tissue mass (FTM), but preferentially at the expense of lean tissue mass. In contrast, pair-fed HFD did not elicit NAFLD in WT mice regardless of sex. Concomitantly, pair-fed HFD oppositely impacted hepatic AEA, 2-arachidonoyl glycerol, and/or CB1 in WT males versus females. In pair-fed HFD mice, liver FA binding protein-1 (Fabp1) gene ablation (LKO): i) exacerbated FTM in both sexes; ii) did not elicit liver neutral lipid accumulation in males and only slightly in females; iii) increased liver AEA in males, but decreased it in females; and iv) decreased CB1 only in males. Thus, pair-fed HFD selectively impacted hepatic ECs more in females, but did not elicit NAFLD in either sex. These effects were modified by LKO consistent with FABP1’s ability to impact EC and FA metabolism.